SNP-based conservation genetics of the southern Swedish brown bear (Ursus arctos) population - Fahlén, Joanna (2014)
Species with small population sizes needs to be managed in order to prevent extinction in the long-term. Genetic monitoring of wild populations over time is important since it enables for management strategies that takes the genetic status into consideration. Non-invasive sampling techniques are useful for rare and elusive species since the organic material containing DNA is collected through, for example, hair, saliva or feces without handling or even disturbing the animal. Single nucleotide polymorphisms (SNPs) are a molecular marker that amplifies well when using low quality or degraded DNA, as often is the case with non-invasive samples. The aim of this thesis is to genetically characterize the previously bottlenecked southern Swedish brown bear population within the counties of Dalarna and Gävleborg. Non-invasively sampled DNA from 434 bears was genotyped on a recently developed SNP-panel with 96 loci. The analyses of genetic diversity resulted in an observed heterozygosity that was close to the heterozygosity expected under ideal conditions (Ho 0.45, He 0.49). There were no indications of inbreeding (mean FIS -0.0014). Seven males from a different population were identified and these males are likely first generation immigrants from the northern population, which indicates gene flow. No population structure within the southern population was found, possibly due to the high mobility among males. The effective population size (Ne) was 74.4 and the Ne/NC ratio 0.094. According to recommendations of Ne, which are set to prevent inbreeding and to ensure long-term viability, the Ne of the southern population could increase. Further gene flow from the northern population will likely enable this scenario.